Challenges of spatial planning in the context of sustainable development - Drzazga, Dominik (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This paper is an attempt to indicate the author's concept of system changes in spatial planning and land use management in Poland. In the introduction to paperwork it is briefly described the evolution of urban planning tools for organizing physical space to instrument which nowadays stimulates spatial development processes and optimize the use of various natural resources(including land). This paper Indicates the need for the integration and application of functional approaches in the spatial planning. In the central part of article, the most significant institutional failure and weaknesses that reduce the effectiveness of the spatial planning system in Poland are described. With them in mind, in the second part of the article the author outlined the concept of changes at the level of local and regional planning. The text ends with a brief summary relating to the conditions which must be met for the introduction of the proposed amendments to the develop the planning system.